Registration of ‘Krib’ new lentil variety in Tunisia - OUJI, Ali; Amri, Moez; Barbouchi, Meriem; Omri, Noura; Khamassi, khalil; Sfayhi, Dorra; Agrawal, Shiv Kumar; Kharrat, Mohamed (Springer Verlag, 2023)
In Tunisia, lentil (Lens culinaris subsp. culinaris Medik.) is cultivated in arid and semi-arid areas. Terminal drought and heat stresses during the end of cycle causes signifcant yield losses. Selec tion of short cycle varieties could be the best option to escape the efect of pre cited abiotic factors. ‘krib’ was developed using both modifed pedigree and bulk methods by INRAT in collaboration with ICARDA. It’s a selection from an advanced F9 line, FLIP2012 196L, which was derived from a cross of ILL590 (early-maturing genotype) with ILL8113 (drought tolerant). During the three consecutive cropping seasons (2014–2017), the increase in yield of ‘krib’ above that of the local checks was about 13 and 15% for ‘kef’ and ‘Boulifa’, respectively. ‘Krib’ is an early fowering (on average~93 d) and early-maturing (on average~138 d) variety. It’s therefore, the earliest variety among the previously released varieties. Its dehulled seed has a protein content of 26.8% which was above that of ‘Kef’ (23.9%). ‘Krib’ showed good agronomic performance under drought conditions and large adaptation for the Tunisian environments. Tested as ILL11171, ‘Krib’ was approved for release and registered in the Tunisian Ofcial Catalogue of Plant Varieties in 2019, based on the superior perfor mance, by the DG/PCQPA, Tunisia. The availability of ‘Krib’ variety to farmers could increase lentil pro duction and ofers the producer aproftable beneft in their cropping systems.